Reducing Welding Defects in Offshore Structural Plates Using Six Sigma and Kaizen - Mas Tangguh Afritza Satya Dwirahardja; Joumil A. Saifudin (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2026)
The welding process on structural plates plays a critical role in the construction of offshore platforms, where joint integrity directly determines the strength, safety, and reliability of the entire structure. In practice, however, welding defects such as Lack of Fusion (LOF), Lack of Penetration (LOP), and Excessive Spatter Inclusion (ESI) continue to occur, indicating that the process has not yet reached a zero-defect condition. This case study addresses the problem by applying the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) framework combined with the Kaizen approach for continuous improvement. Welding data from a single offshore fabrication project were analyzed for the period August 2024 to January 2025, during which 18,754 mm of weld defects were recorded out of 123,030 mm of welding inspected. The average Defects Per Million Opportunities (DPMO) was 45,238, corresponding to a sigma level of 3.24. LOF was the dominant defect, accounting for 50.9% of total defects. Control-chart analysis showed several monthly data points falling outside the control limits, indicating process instability and an urgent need for systematic improvement. A Kaizen-based improvement plan was developed around equipment maintenance, operator-skill enhancement, proper material handling, and standardization of welding procedures. These proposed initiatives are intended to reduce defect rates while cultivating a sustainable, disciplined quality culture. As a single-company, single-project case study, the findings establish a quantitative baseline and improvement roadmap rather than a generalizable industry benchmark; nonetheless, the results indicate that integrating Six Sigma with Kaizen is a promising approach for reducing welding defects, improving joint quality, and supporting long-term process stability in offshore platform fabrication.